Pengaruh Pengetahuan Kewirausahaan Dan E-Commerce Terhadap Minat Berwirausaha Mahasiswa Fakultas Keguruan Dan Ilmu Pendidikan Universitas Ekasakti Padang - Dessyta Gumanti; Reni Respita; Nadya Salsabila Abbas (Kilau Publishing, 2025)
The purpose of this study was to examine the influence of entrepreneurial knowledge and e-commerce on the entrepreneurial interest of students at the Faculty of Teacher Training and Education, Ekasakti University, Padang. This research used a quantitative approach. The population in this study was all students at the Faculty of Teacher Training and Education, Ekasakti University, Padang. Accidental sampling was used to obtain a sample size of 88 students. The results of this study indicate that entrepreneurial knowledge (X_1) and e- commerce (X_2) influence the entrepreneurial interest of students at the Faculty of Teacher Training and Education, Ekasakti University, Padang (Y). The significance value for the simultaneous influence of (X_1) and (X_2) on Y is 0.000 <0.05, and the calculated F-value is 31.884 > Ftable 2.71. This indicates that entrepreneurial knowledge and e-commerce influence the entrepreneurial interest of students at the Faculty of Teacher Training and Education, Ekasakti University, Padang.